1988
DOI: 10.1044/jshr.3101.131
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Reliability and Perceptual Ratings

Abstract: The purpose of this study was to examine the reliability of ratings of perceptual characteristics for 10 ataxic dysarthric subjects. The influence of the occurrence of "deviant" speech parameters on the calculation of reliability coefficients was also explored. Results indicated that overall interobserver agreement levels for minimally trained judges compared favorably to reliability coefficients reported in previous studies. Furthermore, levels of overall agreement were above levels of agreement expected on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…Many researchers consider a PCA of above 80% to denote high reliability. 8,11,21 As the PCA for all of the rating scale groups in both the oromotor and perceptual assessments in both environments were above 93.75%, we feel confident that the inter-rater reliability for both environments was high.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers consider a PCA of above 80% to denote high reliability. 8,11,21 As the PCA for all of the rating scale groups in both the oromotor and perceptual assessments in both environments were above 93.75%, we feel confident that the inter-rater reliability for both environments was high.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the PCA for each of the groups of scales was above 88.54%, indicating high agreement (>80%) between the methods. 8,11,21 Thus, despite some low quadratic weighted κ statistics, the PEA and PCA values would indicate that telerehabilitation assessment of oromotor and perceptual speech characteristics is comparable to FTF assessment. The results from the analysis of the ASSIDS data were positive, with both the percentage sentence intelligibility and CER exceeding the predetermined clinical criteria described by the Hill et al 5 study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] and in the present study], the lower the agreement achieved. Reported agreement values are around 0.80 B one scale value [6,9,10,18]. Darley et al [11] reported intra-judge reliability of 0.85 and inter-judge reliability of 0.84.…”
Section: Introductionmentioning
confidence: 95%
“…If perceptual evaluation is to be considered an effective and reliable aid in diagnosis and classification, it becomes clinically relevant to determine the accuracy of this method when used in isolation. However, few studies have so far tried to diagnose specific dysarthria types with perceptual analysis alone [7,20,21]. Judges blinded to the medical diagnoses listened to audiotapes containing several types of dysarthria and were asked to derive the neurological disease or the dysarthria type for each patient: whatever the response procedure overall accurate identification rates were low, between 19 % and 56 % [20].…”
Section: Discussionmentioning
confidence: 99%